Hungarian Monitoring, 16 September 1988 . [Magyar rádiófigyelő], 1988. szeptember 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Helsinki follow-up talks in Vienna urge clarification of Raoul Wallenberg's fate - Polish situation: an overview - Commentary on the Yugoslav economic situation and opposition between nationalities - Today's Czechoslovak verdict on 1968 - Everyday perestroika in the USSR - Gorbachev speeches in Siberia Domestic Affairs: - Debate around construction of Gabčíkovo-Nagymaros dam; government does not regard investment as question of prestige - Toronto court orders trial against Imre Finta, former commander of Szeged ghetto - Hungarian writers request help from all writers and writers' associations in the world to prevent Romanian village destructions - "Changes for political science" - Conversation about the public sphere - "sequestered" category removed from thousands of publications - Problem of handling dangerous and atomic waste Economy: - An economist on the state treasury - Hungarian-American economic relations Külpolitika - A bécsi utótalálkozón R. Wallenberg sorsának tisztázását sürgették - Lengyel helyzetkép - Kommentár a jugoszláviai gazdasági helyzetről és a nemzetiségi ellentétekről - 1968 mai csehszlovákiai megítélése - A mindennapok peresztrojkája a SZU-ban - Gorbacsov-beszédek Szibériában Belpolitika: - A bős-nagymarosi vízlépcső építése körüli vita; a kormány nem tekinti presztízskérdésnek a beruházás megvalósítását - A torontói bíróság elrendelte a főtárgyalást Finta Imre, a szegedi gettó volt őrparancsnoka ellen - A magyar írók a világ összes íróinak és írószövetségeinek segítségét kérik a romániai falurombolás megakadályozása érdekében - "Változatok a politológiára" - Beszélgetés a nyilvánosságról - Több ezer kiadványról lekerült a "zárolt" jelzés - A veszélyes - és atomhulladék kezelés problémája Gazdaság: - Egy közgazdász az államkasszáról - Magyar-amerikai gazdasági kapcsolatok